Detection emotional problems and child maltreat - Nuñez Herrera, Carmen Rosario (2005)
Emotional problems and maltreat in children from both sexes were detected during 2005 in 22 health centers in Lima. The range of 5 to 9 year- old-boys presented the greatest number of child maltreat cases, followed by the group of 1 to 4 years old, a similar situation is observed in girls from both age group. About emotional problems, the situation turns down. Most case occur in 5 to 9-year-old-girls and 10 % of them are referred to 1 to 4 year-old-children from both sexes. Some preventive intervention strategies are designed in primary and hight, addressed not only to the affected children but also to their parents and teachers.